Mapping the Research Landscape of Green Skills in Vocational Education: A Systematic Literature and Network Analysis - Haen Muhaemanurrohmah; Isma Widiaty (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2026)
Green skills integration in vocational education and training (VET) represents a critical priority for sustainable workforce development, yet systematic understanding of effective implementation approaches remains fragmented. This systematic literature and network analysis (SLNA) integrates dual methodological approaches—bibliometric analysis mapping 314 publications and systematic review synthesizing eleven empirical studies—to comprehensively characterize the research landscape and identify evidence-based strategies for green competency development. The systematic review followed PRISMA 2020 guidelines, searching Scopus database (2014-2025) with two-stage screening yielding eleven studies spanning nine countries. The bibliometric component employed VOSviewer keyword co-occurrence analysis, generating seven thematic clusters with temporal overlay visualization. Systematic findings documented holistic framework superiority over standalone interventions, with comprehensive build-in strategies demonstrating higher effectiveness than retrofitted approaches. Bibliometric networks revealed three-phase field development from foundation (2022-2023) through consolidation (2023-2024) to innovation (2024-2025), with behavioral measurement emerging as newest focus. Dual-source validation confirmed teacher capacity as critical implementation bottleneck. Effective green skills integration requires holistic frameworks, comprehensive build-in strategies, and priority teacher development investment. Future research priorities include longitudinal behavioral studies, climate-specific competency development, and technology integration evaluation.